Pitfalls in the use of laparoscopic staplers to perform subtotal cholecystectomy. (16th April 2013) - Chaudery, Muzzafer; Hunjan, Tia; Beggs, Andrew; Nehra, Dhiren
Abstract : Laparoscopic subtotal cholecystectomy (LSC) is considered to be a safe option in severe cholecystitis with non-discernible anatomy within the Calot's triangle where there is a potential risk of causing injury to the common bile duct. Here we present two cases of gallstone pancreatitis associated with use of an endoscopic stapler during LSC.